Impact of mutual influence while ranking authors in a co-authorship network - Amjad, Tehmina; Daud, Ali; Akram, Atia; Muhammed, Faqir (Kuwait Journal of Science, 2016)
Online bibliographic databases are providing significant resources to conduct analysis of academic social networks.We believe that work of an author is always influenced by work of his or her co-authors. In this study, we investigatethe impact of productivity and quality of work of an author’s co-authors on his or her ranking along with his owncontribution. We propose mutual influence (MI) based ranking method, which ranks authors based on (1) Publicationsof an author, along with impact of publications of his or her co-authors, (2) Normalized author position based Citationsweight, which is calculated from the citations received by an author with respect to position of his or her name in theco-authors list, (3) MINCC that combines the impact of both factors. A series of experiments has been conducted andresults show that proposed approach has capability to ranks authors in a significant way.